ANALYSIS OF THE SUITABILITY OF HORIZONTAL ALIGNMENT TO DRIVER SAFETY LEVEL NEEDS CASE STUDY OF CIGASONG - MAJA ROAD, MAJALENGKA ROAD - Fikri Abdul Muizz; Andri Irfan Rifa'i; Adinda Fajarika (Fakultas Teknik Sipil dan Perencanaan, 2024)
Road geometric design is a way of planning roads geometrically or involves calculating angles with processes. In relation to road geometric planning, it is necessary to examine the suitability of the planning criteria with the applicable guidelines, namely the Road Geometric Planning Guidelines. Therefore, this paper evaluates the geometric design in relation to the geometric design suitability of the existing road, namely Cigasong-Maja Road, and adapts it to the Road Geometric Design Guidelines. In this study the research method used was the research object evaluation research method, namely Cigasong-Maja Road.